TEORI PENYELESAIAN MASALAH INVENTIF (TRIZ) BAGI MATA PELAJARAN REKA BENTUK DAN TEKNOLOGI - Kiong, Tee Tze; Saien, Shanty; Md Yunos, Jailani; Heong, Yee Mei; Mohamad, Mimi Mohaffyza; Azman, Mohamed Nor Azhari; Hanapi, Zaliza (Online Journal for TVET Practitioners, 2018)
The Standard Based Curriculum for Secondary School (KSSM) has been implemented in 2017 by replacing the Integrated Secondary School Curriculum (KBSM). One of the newly introduced subjects is Design and Technology (RBT) which emphasis on inventive problem-solving skills that to be learned by form 2 students by the year 2018. This paper focuses on the process of inventive problem solving that consists of four main phases based on the Theory of Inventive Problem Solving (TRIZ). TRIZ is widely applied in many fields and giant companies, from engineering to business and management. The four main phases of inventive problem solving in the context of RBT are: First phase, identifying the problem root cause (function analysis); Second phase, model of problem (physical contradiction); Third phase, selecting the solution tool (space or time separation method); and Fourth phase, model of solution (Inventive principles). It is hoped that this paper will help and give a holistic and analytic explanation for RBT teachers in Malaysia.